EXPERIMENTALLY ESTABLISHED GEOFLUORIMETERS AND THE FLUORINE REGIME IN GRANITE-RELATED FLUIDS - Aksyuk A.M. (My University, 2002)
An earlier version of the phlogopite geofluorimeter and experimental data on the fluorine distribution between a variety of mica end members were used to develop biotite, Li-mica, and muscovite geofluorimeters, which take into account the complicated chemistry of natural micas and fluids. Based on the determined formula of mica, its crystallization temperature, and the water activity in the natural fluid, the geofluorimeters make it possible to obtain quantitative estimates for the HF concentration in the equilibrium fluid. Data on natural biotite-apatite assemblages were utilized to calibrate an apatite geofluorimeter. Some examples of the geofluorimeter application are given for determining the HF concentrations in fluids related to a diversity of granitoids. The HF concentration in the fluids related to rare-metal leucogranites in central Kazakhstan, biotite granites in the Khangilai Massif in eastern Transbaikalia, and some topaz-bearing granites and rhyolites in Honeycomb Hill and Spor Mountain in the United States appears to be close to 0.06 mol/dm 3. The values of these concentrations cluster around a high-F trend in a logM HF-T diagram and may remain almost unchanging over a broad temperature interval of 500-900°C. With a temperature decrease to 350°C (at the Henderson Mo deposit) and fluid dilution with meteoric waters, the concentrations could decrease to 0.01 mol/dm 3. The Li-F amazonite granites at the Ta-Nb Orlovka and Etyka deposits in eastern Transbaikalia, late veins (dikes) of topaz-zinnwaldite granites at the Akchatau deposit, some topaz-bearing rhyolites of Honeycomb Hill and Spor Mountain are characterized by even higher HF concentrations in the fluid, M HF = 0.4-1.0 mol/dm 3. Conceivably, they define another trend with still higher HF concentrations. The fluids at Santa Rita, Aksug, Shakhtama and other porphyry copper and molybdenum deposits define a low-F trend with concentrations of 0.01-0.0001 mol/dm 3. The M HF values in the fluid decrease along this trend by approximately half an order of magnitude with a temperature decrease from 900 to 500°C. This trend also passes through the composition of fluids from barren granitic complexes in Kazakhstan and a number of granitic massifs in the Eastern Ural Uplift.